Trunk and shoulder emg and lumbar kinematics of medicine-ball side throw and side catch and throw - Francisco J. Vera-Garcia; Iñaki Ruiz-Pérez; David Barbado; Casto Juan-Recio; Stuart M. McGill (Asociación Española de Ciencias del Deporte, 2014)
The objective of this study was to analyze trunk and shoulder muscle activation and lumbar spine kinematics of backward and forward phases during both isolated medicine-ball side throws, and medicine-ball side catch and throw sequences. Thirteen recreationally trained men performed three isolated medicine-ball side throws with 1 min rest between repetitions, and three medicine-ball side catch and throw sequences. Surface electromyography signals were collected bilaterally in seven trunk muscles and in the right side for anterior deltoid and pectoralis major. Spine kinematics were measured using an electromagnetic tracking instrument. The results showed that left external oblique and right anterior deltoid activations reached peak levels above 100% MVC during the forward phase highlighting their important role during side medicine-ball throwing. When both exercises were compared, the amplitude of the lumbar motion and the muscle activation in the backward phase were higher during the medicine-ball side catch and throw than in the medicine-ball side throw. According to these results, the medicine-ball side catch and throw is a high demanding plyometric exercise, which seems more appropriate for high performance throwing and striking athletes than for recreationally trained individuals. Suggestions to reduce back injury risk were provided.